Ionic strength-dependent structural transition of proteins at electrode surfaces - Palecek, Emil; Ostatná, Veronika (Chemical communications (Cambridge, England), 2009)
Using constant current chronopotentiometry we showed that in 50 mM sodium phosphate (pH 7) bovine serum albumin and some other proteins were not significantly denatured at a bare mercury electrode while at higher phosphate concentrations they underwent electric field-driven denaturation on the electrode surface.
Keywords: Potentiometry; elektrody; Phosphates; proteiny; Electrodes; potenciometrie; osmolární koncentrace; Osmolar Concentration; koncentrace vodíkových iontů; fosfáty; Hydrogen-Ion Concentration; Proteins